Portrait of war : - Krass, Peter (John Wiley & Sonc, 2007)
"Eight individuals witnessed more of the American fighting experience during World War I than any other U.S. participant, military or civilian. Commissioned as captains in the American Expeditionary Force (AEF), these brave men - known as the AEF's Eight - risked their lives roaming through occupied zones, blood-soaked battlefields, and the forward trenches to complete a groundbreaking mission: they were the first artist-soldiers to be recruited through official government channels to make a historical record of war." "Portrait of War tells the gripping story of these artist-soldiers for the first time. Drawing upon the graphic letters, diaries, and memoirs the men kept as well as the interviews they conducted, Peter Krass presents a completely different view of the Great War as seen through the eyes of these chosen few, who were determined to capture "the shock and loss and bitterness and blood of it."--BOOK JACKET.